First‐in‐Human Single‐Ascending‐Dose, Multiple‐Dose, and Food Interaction Studies of NRD.E1, an Innovative Nonopioid Therapy for Painful Diabetic Peripheral Neuropathy. Issue 9 (14th June 2022) - Tiecke, Eva; Rainisio, Maurizio; Guentert, Theodor; Müller, Stephan; Hochman, Liat; Kaplan, Eli; Mangialaio, Sara
Abstract: Painful diabetic peripheral neuropathy is characterized by burning, stabbing, or electric shock–type pain, which severely impacts day‐to‐day functioning and quality of life. Here, we report the results of 3 phase I studies with NRD135S.E1 (referred to as NRD.E1), a new, orally available chemical entity, presently developed for the treatment of painful diabetic peripheral neuropathy. The first study was a first‐in‐human, randomized, placebo‐controlled, single‐ascending‐dose study, where NRD.E1 was administered to healthy male subjects in single dosages ranging from 300 to 1200 mg. The second study was a randomized, placebo‐controlled multiple‐dose study, where healthy male subjects received 300 mg of NRD.E1 once daily for 5 consecutive days. The third study was an open‐label food interaction study in healthy men and women following a crossover design, where NRD.E1 was administered under fed and fasted conditions at 40 mg. The studies revealed dose‐dependent absorption, increased exposure to NRD.E1 when administered with food, and no relevant accumulation after once‐daily administration. All 3 phase I studies consistently showed rapid absorption of orally administered NRD.E1 followed by fast elimination, mainly via metabolization (glucuronidation), and small secondary increases in plasma concentrations. NRD.E1 was well tolerated, with no subject discontinuation due to treatment‐emergent adverse events in any study.